PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP MINAT BELI KOPI BUBUK DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA KOPI GUNUNG PASAMAN(GUNPAS) - Asmanella Asmanella; Yulasmi Yulasmi; Selvi Yona Sari (Yayasan Tri Edukasi Ilmiah, 2024)
This research aims to determine and try to analyze the influence of service quality and price on interest in buying ground coffee with consumer trust as an intervening variable in Gunung Pasaman Coffee (GUNPAS). This research is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample of this research are GUN Coffee customers[AS. The research results found. There is a positive and significant influence between Service Quality on Consumer Trust in Gunung Pasaman Coffee (GUNPAS). There is a positive and significant influence between price and consumer confidence in Gunung Pasaman Coffee (GUNPAS). There is a positive and significant influence between Service Quality on Purchase Interest in Gunung Pasaman Coffee (GUNPAS). There is no negative and insignificant influence between price and purchase interest in Gunung Pasaman Coffee (GUNPAS). There is a positive and significant influence between Consumer Trust and Purchase Interest in Gunung Pasaman Coffee (GUNPAS). Consumer Trust does not mediate Service Quality on Purchase Intention. Consumer Confidence mediates Price on Purchase Intention.